2013
DOI: 10.3109/01902148.2013.789572
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of GSTP1 and GSTA1 in the pathogenesis of asthma

Abstract: Reactive oxygen species (ROS) are known aggravating factors for airway inflammation in asthma. Glutathione S-transferases (GSTs) detoxify ROS and toxic compounds in environmental exposures. However, little is known about the regulation of GST and expression of GST subtypes in asthma. The aim of this study was to evaluate how GSTs are regulated in asthma. We observed total GST activity and expression of GST subtypes in murine asthma models and GST expressions in induced sputum cells of asthmatics. Total GST act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The ability of Pb to induce oxidative stress in lung cells in the current study is evidenced by the ability of Pb treatment to decrease the expression of GSTA1, a well-known antioxidant gene, and to increase the ROS generation. Our results were in agreement with previous studies showed that changes in the expression levels of antioxidant protein GSTA1 play a key role in the induction of lung inflammation (Rahman and Adcock 2006;Sohn et al 2013). Furthermore, a significant reduction in the antioxidant gene, GSTA1 mRNA expression level was demonstrated in people chronically exposed to environmental heavy metals (Al Bakheet et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The ability of Pb to induce oxidative stress in lung cells in the current study is evidenced by the ability of Pb treatment to decrease the expression of GSTA1, a well-known antioxidant gene, and to increase the ROS generation. Our results were in agreement with previous studies showed that changes in the expression levels of antioxidant protein GSTA1 play a key role in the induction of lung inflammation (Rahman and Adcock 2006;Sohn et al 2013). Furthermore, a significant reduction in the antioxidant gene, GSTA1 mRNA expression level was demonstrated in people chronically exposed to environmental heavy metals (Al Bakheet et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to GSTP, other GSTs have been linked to inflammatory lung diseases and NF-κB activation. In addition to GSTP, GSTA and GSTM are also expressed in lung epithelial cells [38] . A recent study demonstrated that GSTM positive humans display higher NF-κB activity and airway neutrophilia following allergen challenge, as compared to GSTM deficient humans [39] .…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of glutathione S-transferases (GSTs), a supergene family implicated in detoxification of reactive oxygen species that appear to be related to asthma susceptibility [31]. Apparently, some mutations of GSTs may be related to asthma onset and AHR, however, contradictory data was found depending on the study group [32,33]. In fact, Piacentini et al [32] did not find an association between GSTT, GSTM and GSTP (glutathion S-transferases) gene polymorphisms and the development of asthma in an adult Italian population.…”
Section: Clinical Biomarkers Associated With Allergic Asthmamentioning
confidence: 99%